Singular Minimal Translation Surfaces in Euclidean Spaces Endowed with Semi–symmetric Connections - Aydin, Muhittin Evren; Kara, Ayla Erdur; Ergut, Mahmut (Association of Mathematicians (MATDER), 2021)
In this paper, we study and classify singular minimal translation surfaces in a Euclidean space of dimension 3 endowed with a certain semi-symmetric (non-)metric connection. © MatDer.
Keywords: semi–symmetric connection; Singular minimal surface; translation surface; ?–catenary